Promoting Inclusivity of LGBTQ Students and Classroom Community through English Language Arts - Steiner, Randi (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2021)
This article addresses the need for early elementary educators ranging from kindergarten through fifth grade to include English Language Arts lessons that are inclusive of Lesbian, Gay, Bisexual, Transgender, Queer and Questioning (LGBTQ) topics, as well as methods on how to incorporate them. Research has shown that most schools lack curriculum that includes LGBTQ characters or topics. Supporting LGBTQ students has the potential to help their social-emotional well-being, as well as help their peers become more empathetic towards people who are different from them, thus positively impacting the school environment. Elementary educators can help foster inclusivity and encourage acceptance by implementing these lessons. Educators can use children’s literature that includes characters and story lines that address LGBTQ topics and themes.